Antibiotics in childhood pneumonia: how long is long enough? - Grimwood, Keith; Fong, S.M.; Mong, How Ooi; Nathan, Anna M.; Chang, Anne B. (BioMed Central, 2016)
Improved access to healthcare, vaccines and treatment with antibiotics has reduced global mortality from childhood community-acquired pneumonia. However, as respiratory viruses are responsible for most episodes of pneumonia, important questions remain over who should receive these agents and the length of each treatment course. Worldwide concerns with increasing antibiotic resistance in respiratory pathogens and appeals for more prudent antibiotic prescribing provide further urgency to these clinical questions. Unfortunately, guidelines for treatment duration in particular are based upon limited (and often weak) evidence, resulting in national and international guidelines recommending treatment courses for uncomplicated pneumonia ranging from 3 to 10 days. The advantages of shortcourse therapy include a lower risk of developing antibiotic resistance, improved adherence, fewer adverse drug effects, and reduced costs. The risks include treatment failure, leading to increased short- or long-term morbidity, or even death. The initial challenge is how to distinguish between bacterial and non-bacterial causes of pneumonia and then to undertake adequately powered randomised-controlled trials of varying antibiotic treatment durations in children who are most likely to have bacterial pneumonia. Meanwhile, healthcare workers should recognise the limitations of current pneumonia treatment guidelines and remember that antibiotic course duration is also determined by the child’s response to therapy.